Sonoelastographic Findings of Mucocele-Like Lesion in Breast Due to AQUAfilling® Gel Injection. (November 2021) - Basara Akin, Isil; Ozgul, Hakan; Guray Durak, Merih; Gurel, Duygu; Sevinc, Ali Ibrahim; Balci, Pinar
AQUAfilling ® gel has been described as human tissue biocompatible sterile synthetic material. In the literature, there are some cases presenting the complications of gel application. Rupture of implant, leakage, and migration of the gel are the most common complications. The radiologic findings due to gel leaking may mask many breast lesions including malignancy. In this case, the aim was to present the sonographic findings and elastographic features of a histopathologic-proven mucocele-like lesion in breast, due to AQUAfilling ® gel injection. This appears to be a rather unique case in the literature.